Relationship of the anterior ethmoid sinus to the lacrimal sac: a computed tomography study - Beatriz de Costa Remor; Leonardo Balsalobre; Simone Haber Duellberg Von Faber Bison; Maria Helena Salgado Delamain Pupo Nogueira; Ana Taíse de Oliveira Meurer; David Caetano Bastos; Aldo Cassol Stamm (Brazilian Journal of Otorhinolaryngology, 2022)
Objective: To analyze the anatomical relationship between the lacrimal sac and the agger nasi cell on Computed Tomography (CT); to correlate the right and left sides on each scan. Methods: CT scans of adult patients were reviewed for pneumatization of the agger nasi and its relationship to the lacrimal sac. The degree of agreement between the right and left sides was also evaluated. Results: A total of 130 CT scans were examined. An agger nasi cell was found medial to the lacrimal sac in 59.23% of scans. On 86.15% of scans, pneumatization was similar on both sides. Conclusion: The agger nasi air cell is located medial to the lacrimal sac in more than half of individuals. The right and left sides exhibit the same pneumatization pattern in approximately 80% of cases. Level of evidence: 4.